Bending performance of prefabricated ultra-thin UHPC unit plate reinforced orthotropic steel bridge decks - Zhou, Xiang; Jiang, Jinlong; Liu, Le; Wang, Shan; Deng, Xilei; Li, Yong; Zhang, Zhongya (Frontiers in Materials, 2024)
To address the challenges related to lengthy construction period, complex maintenance requirement, and the elevated risk of shrinkage cracking associated with cast-in-place UHPC reinforcement of orthotropic steel bridge decks. This paper proposes a novel solution that prefabricated ultra-high-performance concrete (UHPC) slab with epoxy bond connection is used as a reinforcement layer for orthotropic steel bridge decks. Four sets of bending tests on composite bridge deck were carried out to compare the flexural performance of composite bridge decks under different joint forms and loading patterns.The results indicate that the precast UHPC decks delaminated from the epoxy bonding layer without failure of the epoxy layer itself in all cases. The positive bending capacity of the jointless composite bridge deck is approximately 27.67 kN, while the negative bending capacity is around 16.58 kN. For the composite bridge deckwith epoxy adhesive joints (EA-J-Ln), the negative bending capacity is 2.54 kN, and the negative bending capacity of the joint area reinforced with carbon fiber cloth (EA-JC-Ln) is increased to 4.17 kN. Therefore, the use of carbon fiber cloth can significantly improve the bending resistance of the joints. Finally, numerical model of the composite deck based on Cohesive Zone Model (CZM) was established, validating the applicability of this simulation method in the novel composite bridge deck.